A high‐fat diet rich in corn oil induces cardiac fibrosis in rats by activating JAK2/STAT3 and subsequent activation of ANG II/TGF‐1β/Smad3 pathway: The role of ROS and IL‐6 trans‐signaling. Issue 8 (20th June 2019) - Eid, Refaat A.; Alkhateeb, Mahmoud A.; El‐Kott, Attalla Farag; Eleawa, Samy M.; Zaki, Mohamed Samir Ahmed; Alaboodi, Sultan Abdullah; Salem Al‐Shudiefat, Abd Al‐Rahman; Aldera, Hussain; Alnamar, Nada Mohammad; Alassiri, Mohammed; Khalil, Mohammad A.
Abstract: This study compared the effect of low‐fat diet (LFD) and high‐fat diet rich in corn oil (HFD‐CO) on left ventricular (LV) fibrosis in rats and examined their effect of angiotensin II (ANG II), JAK/STAT, and TGF‐1β/smad3 pathways. As compared to LFD which didn't affect any of the measured parameters, HFD‐CO‐induced type 2 diabetes phenotype and increased LV collagen synthesis. Mechanistically, it increased LV levels of ROS, ANG II, ACE, IL‐6, s‐IL‐6Rα, TGF‐β1, Smad‐3, and activities of JAK1/2 and STAT1/3. AG490, a JAK2 inhibitor, partially ameliorated these effect while Losartan, an AT1 inhibitor completely abolished collagen synthesis. However, with both treatments, levels of ANG II, IL‐6, and s‐IL‐6Rα, and activity of JAK1/STAT3 remained high, all of which were normalized by co‐administration of NAC or IL‐6 neutralizing antibody. In conclusion: HFD‐CO enhances LV collage synthesis by activation of JAK1/STAT3/ANG II/TGF‐1β/smad3 pathway. Practical applications: We report that chronic consumption of a high‐fat diet rich in corn oil (HFD‐CO) induces diabetes mellitus phenotype 2 associated with left ventricular (LV) cardiac fibrosis in rats. The findings of this study show that HFD‐CO, and through the increasing generation of ROS and IL‐6 levels and shedding, could activate LV JAK1/2‐STAT1/3 and renin‐angiotensin system (RAS) signaling pathways, thus creating a positive feedback between the two which ultimately leads to activation of TGF‐1β/Smad3 fibrotic pathway. Herein, we also report a beneficial effect of the antioxidant, NAC, or IL‐6 neutralizing antibody in preventing such adverse effects of such HFD‐CO. However, this presents a warning message to the current sudden increase in idiopathic cardiac disorders, especially with the big shift in our diets toward n‐6 PUFA. Abstract : A high‐fat diet rich in corn oil (HFD‐CO) enhances cardiac levels of reactive oxygen species (ROS), interleukin‐6 (IL‐6), and soluble‐IL‐6 receptor‐α1 (sIL‐6Rα1) which leads to activate JAK2/STAT3 signaling. This increased the activity of renin‐angiotensin system (RAS) by increasing the transcription of angiotensin I (ANG I), angiotensin‐converting enzyme (ACE), and ANG receptor 1 (AT1) which in turn, in a positive feedback, activates JAK1/2‐STAT1/3 and transforming growth factor (TGF‐β1)/smad3 signaling pathways to induce cardiac fibrosis.